PENGARUH MODAL INTELEKTUAL, DANA PIHAK KETIGA, DAN NON PERFORMING LOAN TERHADAP PROFITABILITAS - Stephanie Carolina; Novera Kristianti Maharani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Profitability is very important for the company for its survival. The purpose of this study was to determine the effect of intellectual capital, third party funds, and non-performing loans on the profitability of banking sector companies listed on the Indonesia Stock Exchange in 2018-2022. The implementation of this research uses a causality associative research design with secondary data types. The sampling technique used purposive sampling and obtained as many as 23 companies that meet the criteria that generate profits and have intellectual capital data from a total population of 55 companies with a research period of 115 years, so that 115 sample data were obtained. This study utilizes a multiple linear regression analysis model. The results showed that intellectual capital has a positive effect on profitability as measured using the value added intellectual coefficient (VAIC), third party funds have a positive effect on profitability by adding up demand deposits, savings and deposits. Then non-performing loans have a negative effect on profitability. Future researchers are expected to consider or add other variables that can affect profitability, such as sales growth, leverage, dividend policy, inflation rates and interest rates on different research objects. Factors from intellectual capital, third party funds, and non-performing loans can be used as the main reference for companies in an effort to increase their profitability.